Pore structure evolution in andesite rocks induced by freeze–thaw cycles examined by non-destructive methods - M. Maľa (Scientific Reports, 2022)
Abstract In this paper, we compare the values of petrophysical properties before and after 100 freeze–thaw (F–T) cycles, as well as recorded length change behaviour and temperature development on a vacuum-saturated fractured andesite rock sample taken from the Babina Quarry in Slovakia using a specially-constructed thermodilatometer, VLAP 04, equipped with two HIRT-LVDT sensors. We also used non-destructive visualization of the rock pore network by µCT imaging in order to study the development of the pore structure and fracture network in pyroxene andesites during the freeze–thaw process. The results show that the andesite rock samples, due to good fabric cohesion, low porosity, and low pore interconnection, showed good resistance against frost-induced damage. However, it must be stated that the main process causing disintegration of this type of rock is fracture opening, which is caused by internal stresses induced by water–ice phase transition. The overall residual strain recorded after 100 F–T cycles was not significant, however, the increase of 31 pp in volume of the fracture showed us that repeated freezing and thawing can lead to long term deterioration in terms of subcritical crack growth in brittle-elastic solids like pyroxene-andesite rocks.